Multidimensional Challenges of Informal Services for Elderly with Disabilities - Rohman, Yani Fathur; Kiswanti, Utin; Putri, Myranda Zahra (Indonesian Journal of Disability Studies, 2025)
Indonesia is predicted to start experiencing a nationwide aging population by 2035. An increase in the elderly population is synonymous with physical and mental decline and the risk of becoming disabled. This research aims to explore the complexity of the challenges of elderly with disabilities and efforts to realize social inclusion. This research uses a qualitative method with a case study approach. Data collection was carried out through Focus Group Discussion (FGD) with several relevant regional apparatus organizations including the Regional Development Planning Agency and the Social Service of Yogyakarta Province. The findings of this study show that the complexity of the challenges of elderly disabilities is the result of the intersection between cultural and structural aspects. Therefore, it is necessary to explore the challenges of the elderly with disabilities in the perspective of social exclusion, especially related to the discourse of redistribution and moral underclass